The discovery of Dutch identity A critical exploration - Versteeg, Peter (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
Since 2001, questions of national and cultural identity have become central concerns in the public debate in the Netherlands and in Dutch politics. Although the culture and lifestyles of migrants were socially and politically recognised as a distinct identity over the years, Dutch identity was hardly definable. Gradually, things seem to have turned around. Post-2001, Netherlands migrant identities have become problematic, particularly the identities of people from a Muslim background. At the same time, a substantial number of Dutch have started to emphasise Dutchness, along with a call for an assimilation of difference. In this paper, I trace how and why identity formation in the Netherlands has changed. The Netherlands thus prove to be an interesting example of the understanding that identity is situational and contextual. I conclude with the remark that our understanding of how identity formation works, without precluding a critical judgment of that process.